Trends Of Baseline Cd4 Counts at The Time of Registration of Adult Patient, Who Are Put on Ante Retroviral Therapy in India - Ugra Mohan Jha; Sukarma Tanwar; B.B Rewari; AS Rathore; Laxmikant Chavan; Neeraj Dhingra (Medsci Publications, 2016)
Background:  India has shown considerable progress in prevention and treatment of HIV/AIDS, but timely detection and linkage to HIV treatment still remain a challenge. Understanding the baseline CD4 count level of patients at the time registration, who are put on ART with its trends and associated risk factors, could potentially guide program strategy. Methods: Data on the levels and trends of baseline CD4 count level of adult (>15 years of age) patients at the time registration are drawn from the patient level data entered in PLHA software from 2007 to 2011. Results: Out of 727,280 adult patient registered during 2007- 2011; 76.3% were initiated on ART. The baseline median CD4 count levels of adult patients, who were initiated on ART shows increasing  trend during 2007-2011. Gender wise, baseline cd4 count over the year has found significantly higher CD$ in female (p<0.05). In this study also report patient having over 250 cells/mm3 CD4 count have increased during the period 2007 to 2011. Conclusion: The results indicate increase in median cd4 count level of adult patient registered and put on ART over the year. However, consolidation of universal access to treatment to all is highly felt need.